Expectations and feelings of pregnant and postpartum women who tested positive for SARS-CoV-2 (Research, Society and Development, 2024)
The objective of this study is to analyze the feelings experienced by pregnant and postpartum women who contracted SARS-CoV-2 during the perinatal period. This is an exploratory study with a qualitative, quantitative, and descriptive approach. It was conducted at the Women's Health Center and the Specialty Medical Clinic from August 2022 to November 2022, with a study sample of pregnant and postpartum women who tested positive for SARS-CoV-2 during the pandemic period. Data were collected through semi-structured interviews with the participants. The analysis was carried out by characterizing the clientele and categorizing the women's responses to form the analytical categories of the study, to be discussed according to relevant literature. The present study was submitted to the Ethics and Research Committee of the University Center of Valença (UNIFAA), under CAAE number 61744522.6.0000.5246, and was approved by opinion 5.608.015. Fourteen postpartum women who had contracted SARS-CoV-2 while classified as pregnant participated in the study. Three categories of analysis were created: 1) “The anxieties of postpartum women who tested positive while pregnant and their reception by healthcare professionals”; 2) “The feelings and fears upon receiving a positive result and the current state of these women following their experiences”; and 3) “Difficulties, challenges, and deprivations encountered with the confirmation of the SARS-CoV-2 diagnosis.” The study concludes that the predominant feelings experienced by postpartum women who contracted SARS-CoV-2 during pregnancy were fear, anxiety, and anguish due to pregnancy and the possible complications associated with the virus.